New instrument for measuring quality of life in patients with cervical cancer. Issue 7 (7th September 2021) - Jankovic, Slobodan; Zivkovic Zaric, Radica; Krasic, Katarina; Opancina, Valentina; Nedovic, Nikola; Zivkovic Radojevic, Marija
Abstract: Our study aimed to develop and validate a reliable instrument that can measure the quality of life (QOL) of patients with cervical cancer living in a developing country, such as the Central Balkan country, Serbia. Our study was cross-sectional for assessing the reliability and validity of a questionnaire. Balkan questionnaire for QOL of patients with cervical cancer showed satisfactory reliability and temporal stability. When the investigators rated the questionnaire, Cronbach's alpha was 0.971 at the beginning, and one month later it was 0.967. When the questionnaire was rated by patients themselves, Cronbach's alpha was 0.972. The questionnaire should be considered as an addition to the existing armamentarium for measuring the quality of life in patients with cervical cancer.